Reproduction record of captive Sumatera elephant (Elephas maximus sumatranus) at Way Kambas National Park, Indonesia - Sofie Adi, Keren Jayanti; Budiarto Budiarto; Hermin Ratnani; Pudji Srianto; Budi Utomo; Suzanita Utama; Setiawan Koesdarto; Nurhusien Yimer (Ovozoa: Journal of Animal Reproduction, 2023)
This research aims to determine reproductive data on Sumatran elephants (Elephas maximus sumatranus) in the ETC and ERU of Way Kambas National Park, Indonesia during 1988-2021. Data recorded from the elephant population at both locations (ETC and ERU) includes the number, gender of elephants, elephant calves, ages and birth dates. Calving intervals and service periods were calculated from calving records of cows with a minimum parity of two. Data collection produced data on 47 elephant calves from 13 female elephants with at least twice the parity and 12 primiparous cows. Elephant reproductive records at ETC and ERU were: age (37.44 ± 9.03 vs. 29.75 ± 3.30 years), parity (2.78 ± 1.09 vs. 2.50 ± 0.58), and age at first birth (18, 11 ± 3.92 vs. 17.75 ± 0.50 years). While the calving interval was 1857.56 ± 870.81 vs. 1833.00 ± 305.18 days, and service period respectively 1229.44 ± 846.18 vs. 1210.50 ± 283.59 days, respectively. It can be concluded that the calving interval and service period for captive elephants at ETC and ERU were not much different and were within the normal range. Young cows showed better reproductive efficiency than older cows. Monitoring calves is very important. Further assistance is needed to improve elephant mobile veterinary services, increase diagnostic laboratory capacity, and educate camp managers, veterinary assistants, and mahouts about elephant diseases, their monitoring and treatment. In addition, the use of reproductive technology such as monitoring ovulation using ultrasound and carrying out artificial insemination was expected to increase reproductive efficiency.